Effects of Ocean Acidification on Carbon and Nitrogen Fixation in the Hermatypic Coral Galaxea fascicularis - Zheng, Xinqing; Wang, Chenying; Sheng, Huaxia; Niu, Gaofeng; Dong, Xu; Yuan, Lingling; Shi, Tuo (Frontiers in Marine Science, 2021)
The supply of metabolites from symbionts to scleractinian corals is crucial to coral health. Members of the Symbiodiniaceae can enhance coral calcification by providing photosynthetically fixed carbon (PFC) and energy, whereas dinitrogen (N2)-fixing bacteria can provide additional nutrients such as diazotrophically-derived nitrogen (DDN) that sustain coral productivity especially when alternative external nitrogen sources are scarce. How these mutualistic associations benefit corals in the future acidifying ocean is not well understood. In this study, we investigated the possible effects of ocean acidification (OA; pHs 7.7 and 7.4 vs. 8.1) on calcification in the hermatypic coral Galaxea fascicularis with respect to PFC and DDN assimilation. Our measurements based on isotopic tracing showed no significant differences in the assimilation of PFC among different pH treatments, but the assimilation of DDN decreased significantly after 28 days of stress at pH 7.4. The decreased DDN assimilation suggests a nitrogenous nutrient deficiency in the coral holotiont, potentially leading to reduced coral calcification and resilience to bleaching and other stressful events. This contrasting impact of OA on carbon and N flux demonstrates the flexibility of G. fascicularis in coping with OA, apparently by sustaining a largely undamaged photosystem at the expense of N2 fixation machinery, which competes with coral calcification for energy from photosynthesis. These findings shed new light on the critically important but more vulnerable N cycling in hospite, and on the trade-off between coral hosts and symbionts in response to future climate change.